Risk of underlying chronic medical conditions for invasive pneumococcal disease in adults. Issue 36 (5th August 2016) - Baxter, Roger; Yee, Arnold; Aukes, Laurie; Snow, Vincenza; Fireman, Bruce; Atkinson, Bruce; Klein, Nicola P.
Highlights: We estimated IPD relative risk (RR) for non-immunocompromising (IC) conditions. We also estimated IPD RR for more than one non-IC condition. RR for a single non-IC medical condition: twofold the general KPNC population RR. IPD RR for multiple non-IC conditions increased with each additional condition. Abstract: Purpose: In the United States, the 13-valent pneumococcal conjugate vaccine is recommended in persons ⩾65 years of age, and persons ⩽65 years of age with immunocompromising (IC) conditions. For invasive pneumococcal disease (IPD) prevention in those ⩽65 with non-IC medical conditions, the 23-valent polysaccharide vaccine is recommended. This group is at higher risk of IPD than the general population, but the level of risk is not well-quantified. We estimated IPD risk by individual underlying medical conditions, and by total number of conditions, for persons ⩾18 years of age. We calculated the relative risks (RR) of various medical conditions, comparing the incident IPD cases to the general study population, and used Poisson regression models to estimate an IPD RR, adjusting for other conditions. We also examined IPD incidence by number of conditions diagnosed in each calendar year, using a risk-stacking model. Results: Underlying medical conditions with the highest adjusted RR for IPD were chronic liver disease (RR 2.1, 95% CI 1.5–2.8) and chronic obstructive pulmonary disease (COPD; RR 2.1, 95% CI 1.8–2.5). IPD risk increased with increasing number of medical conditions: adjusted RR, 2.2 (95% CI 1.9–2.5) 1 condition, 2.9 (2.5–3.5) for 2 conditions, and 5.2 (4.4–6.1) for 3 conditions. Conclusions: For persons with a single, non-IC medical condition, IPD risk was twice that for the general KPNC population. Persons with multiple, non-IC chronic conditions exhibited increased IPD risk with each additional condition. Such information may inform discussions on recommendations for adult pneumococcal immunization and prevention.